ISOLATION, CHARACTERIZATION, AND IDENTIFICATION OF BIOACTIVE COMPOUNDS IN SIX MEDICINAL PLANTS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Natural Products from medicinal plants either as pure or as a standardized extracts provide unlimited opportunities for new  drugs  because  of  the  unmatched  availability  of  chemical constituents. Since ancient times, natural products   have  been utilized to treat and cure chronic diseases like cancer, diabetes, asthma,  anti-inflammatory,  analgesic  and  as  alternatives  for hormone  replacement  therapy   worldwide.    According   to  the World  Health  Organization  (WHO),  more   than  80%  of  the world's  population   relies   on   traditional  medicine  for   their primary healthcare needs. Despite their widespread existence, the variety of bioactive natural products in natural medicines are not sufficient.  Today,  it  is  very  crucial  to   develop  effective  and selective methods for the extraction and isolation of new natural products.   The  focus   of  this  review  paper   is  to  provide   a comprehensive  view  on  the  analytical  methodologies,   which include extraction, isolation and characterization of the natural products from  medicinal plants  and  common  phytochemical screening assays.